Prospects and Health Promoting Effects of Brown Algal-derived Natural Pigments - ratih pangestuti; Singgih Wibowo (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2013)
Recently, a great deal of interest has been developed to isolate novel bioactive compounds from marine resources. Among marine resources, marine brown algae are considered valuable sources of structurally diverse bioactive compounds such as chlorophylls and carotenoids. Chlorophyll has been known for its antioxidant activity; meanwhile carotenoid is well known for its anticancer and anti-obesity properties. Therefore, marine brown algal-derived natural pigments have great potential for further development of valuable products in nutraceutical, and pharmaceutical areas. This contribution presents an overview of potential health benefits properties, and prospects of natural pigments derived from marine brown algae. Keywords: Marine algae, natural pigments, nutraceutical, pharmaceutical.